Strategi Pembinaan Akhlakul Karimah di Sekolah - Nashihin Nashihin; Ahmad Afan Zaini (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2023)
This study aims to: 1) describe the strategy of Islamic religious education teachers in fostering students' Akhlakul Karimah; 2) describe the activities carried out by Islamic religious education teachers in fostering students' Akhlakul Karimah; 3) identify the factors that support and hinder the strategy of Islamic religious education teachers in fostering students' Akhlakul Karimah. This research is a qualitative research using a descriptive approach. The techniques used in collecting data through observation, interviews and documentation. The research instrument is the researcher himself as the main instrument where the researcher uses his logic to be able to verify or draw conclusions about an existing problem. The results showed that: 1) Activities carried out by Islamic religious teachers in fostering students' akhlakul karimah included PHBI activities, dhuha prayers, congregational dhuhur prayers, reading blessings, murajaah, Alms Saturday Movement, istighatsah and tahlil; 2) The strategy of Islamic religion teachers in fostering students' Akhlakul Karimah is implemented in the teaching and learning process using several methods including habituation, exemplary, personal approach, advice and punishment; 3) Factors driving the formation of akhlakul karimah students include the support of all school members, the support of student guardians, being in a boarding school environment and student self-awareness. While the inhibiting factors are different educational, social and economic backgrounds, and the busy activities at Islamic boarding schools.